Habitual physical activity of independently ambulant children and adolescents with cerebral palsy: Are they doing enough? - Mitchell, L.; Ziviani, J.; Boyd, Roslyn (American Physical Therapy Association, 2015)
© 2015 American Physical Therapy Association.Background: Despite the health benefits of regular physical activity, children with cerebral palsy (CP) are thought to participate in reduced levels of physical activity.Objective: The study objective was to assess physical activity and determine the proportion adhering to the recommended 60 minutes of moderate-to-vigorous physical activity (MVPA) daily in independently ambulant children and adolescents with unilateral CP.Design: This was a cross-sectional study.Method: Children (N=102; 52 boys, 50 girls; mean age=11 years 3 months, SD=2 years 4 months) with spastic hemiplegia classified at Gross Motor Function Classification System (GMFCS) levels I (n=44) and II (n=58) recorded physical activity over 4 days using an accelerometer. Activity counts were converted to daily and hourly time spent inactive and in light physical activity or MVPA using uniaxial cutpoints (inactive: =100 vertical counts=min-1, light: 101 to 2,295 vertical counts·min-1, MVPA: -2,296 vertical counts=min-1) and recorded step counts. Differences between groups were examined using t tests.Results: Of a potential 396 days, 341 days (86%) were recorded. The average wear time was 11:44 (SD=1:56) hours. On a typical day, participants recorded 438 (SD=234) counts=min-1, took 7,541 (SD=3,894) steps, spent 8:36 (SD=1:09) hours inactive, spent 2:38 (SD=0:51) hours in light activity, and spent 0:44 (SD=0:26) hours in MVPA. Only 25% of participants met the recommended level of MVPA on at least one day. Physical activity was highest in boys (versus girls), in children (versus adolescents), and on weekdays (versus weekends).Limitations: Participants were limited to children with unilateral spasticity who were classified at GMFCS levels I and II.Conclusions: The majority of independently ambulant children with unilateral CP did not perform sufficient physical activity to meet public health recommendations.